The potential of banana corm-based (Musa Paradisiaca) instant noodles as a solution-oriented strategy for implementing a circular economy for sustainable prosperity - Aurellino Lawrence Nugroho; Alexandra Earlita Prabadewi; Yosua Latreia Irawan (Institute for Advanced Science, Social, and Sustainable Future (IASSSF), 2026)
Background: The accumulation of agricultural waste and high dependency towards wheat imports remains a structural challenges to food security and environmental sustainability. Banana corm, an underutilized by-product rich in starch and resistant starch content, offers a strategic potential as a functional substitute for wheat in instant noodle production. The goal of this research is to bridge these gaps by formulating Miglo and simultaneously evaluating its potential to harmonize physicochemical quality with real-world economic viability. Methods: This mixed-method research applying a Completely Randomized Design with three substituion levels (30-50%) where physicochemical properties were analyzed descriptively while organoleptic data underwent One-Way ANOVA and Duncan’s test. Socio-economic impacts were assessed through field observations to validate the circular economy’s feasibility. Findings: The result showed that 50% substitution (T3) yielded the highest consumer acceptance, despite its decrease in carbohydrate due to resistant starch formation. Aroma and texture remained statistically unaffected, proving that high levels of substitution do not compromise overall sensory quality. Miglo implementation demonstrates economic feasibility, offering a strategic solution for agricultural waste valorization and reduced wheat dependency within a functional circular economy framework. Conclusion: Instant noodles made from banana corms (Musa paradisiaca) are an innovative circular economy strategy that is acceptable to consumers when made from a 50% wheat flour and 50% banana corm flour mixture. This strategy has a positive impact on reducing agricultural waste, strengthening food security, and improving the economic welfare of the community. Novelty/Originality of this article: This research provides an integrative approach bridging technical aspects and practical impacts of the circular economy model, serving as a strategic solution to ensure food sovereignty and community economic empowerment.